2022
DOI: 10.48550/arxiv.2203.00636
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Distributional Reinforcement Learning for Scheduling of Chemical Production Processes

Abstract: Reinforcement Learning (RL) has recently received significant attention from the process systems engineering and control communities. Recent works have investigated the application of RL to identify optimal scheduling decision in the presence of uncertainty. In this work, we present a RL methodology tailored to efficiently address production scheduling problems in the presence of uncertainty. We consider commonly imposed restrictions on these problems such as precedence and disjunctive constraints which are no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 44 publications
0
2
0
Order By: Relevance
“…Fig. 37 and 38 show one idea proposed in recent work 221 and a corresponding schedule generated for the case study detailed there.…”
Section: Reaction Chemistry and Engineering Reviewmentioning
confidence: 99%
“…Fig. 37 and 38 show one idea proposed in recent work 221 and a corresponding schedule generated for the case study detailed there.…”
Section: Reaction Chemistry and Engineering Reviewmentioning
confidence: 99%
“…However, some well-known drawbacks limit the use of such AI approaches in complex industrial scheduling: (a) guaranteeing state constraints is difficult; (b) the scale is limited to small/medium size problems, otherwise the action-state space is extremely large to approximate a value function fairly enough; (c) learning optimal policies under uncertainty requires having a detailed simulation model to create extensive virtual data from thousands of runs with different state-input situations; (d) any change in the actual system structure (e.g., a new constraint or product) requires generating new valid data and re-training the AI model. In fact, the authors of a related work report that mixed-integer linear programming (MILP) outperforms reinforcement learning (RL) in terms of optimality, despite having done policy training with about 450,000 simulations of the uncertain model. Note also that such an optimality gap was already reported in a problem of about a thousand decision variables and the industrial case study tackled in this paper has more than five thousand, as will be shown in the next sections.…”
Section: Introductionmentioning
confidence: 99%